Carbon Footprint Management of Road Freight Transport under the Carbon Emission Trading Mechanism. (7th September 2015) - Li, Jin; Lu, Qihui; Fu, Peihua
Abstract : Growing concern over environmental issues has considerably increased the number of regulations and legislation that aim to curb carbon emissions. Carbon emission trading mechanism, which is one of the most effective means, has been broadly adopted by several countries. This paper presents a road truck routing problem under the carbon emission trading mechanism. By introducing a calculation method of carbon emissions that considers the load and speed of the vehicle among other factors, a road truck routing optimizing model under the cap and trade mechanism based on the Travelling Salesman Problem (TSP) is described. Compared with the classical TSP model that only considers the economic cost, this model suggests that the truck routing decision under the cap and trade mechanism is more effective in reducing carbon emissions. A modified tabu search algorithm is also proposed to obtain solutions within a reasonable amount of computation time. We theoretically and numerically examine the impacts of carbon trading, carbon cap, and carbon price on truck routing decision, carbon emissions, and total cost. From the results of numerical experiments, we derive interesting observations about how to control the total cost and reduce carbon emissions.